Assessment of the efficacy of stable liquid chlorine dioxide (CLO2) in disinfection of stored table eggs (VETERINARIA, 2025)
Microbiological contamination of table egg shells poses an importantpublic health and technological challenge, particularly in the EuropeanUnion, where washing and disinfection of Class A eggs are prohibiteddue to adverse effects associated with previously used sanitisingagents. This study evaluated the efficacy of stable liquid chlorinedioxide (ClO₂) in reducing microbial load on eggshells during storageunder commercial conditions. A total of 200 eggs were dividedinto two groups: a control group (untreated) and an experimentalgroup treated with a fine aerosol of 50 ppm ClO₂. Microbiologicalcleanliness was assessed using total aerobic mesophilic bacterial count(UBAMB) and luminometry at predetermined intervals.Immediatelyafter treatment (day 0), the experimental group showed a pronouncedmicrobiological reduction, with median UBAMB values decreasingfrom 35,000 CFU in the control group to 70 CFU in the treated group(p = 0.029). Significant differences in luminometry values betweenthe groups were observed on days 0 and 14 (p = 0.028; p = 0.025),indicating sustained antimicrobial activity during storage. Within theexperimental group, luminometry values showed significant temporalvariation (p = 0.015), characterised by an increase by day 7, followedby stabilisation by day 14, when values returned to levels comparableto those observed immediately after disinfection (p = 0.980). Nosignificant temporal changes were detected in the control group (p =0.276). Stable liquid chlorine dioxide proved to be an effective andtechnologically acceptable disinfectant, achieving significant microbialreduction without compromising egg integrity. These findings highlightthe potential applicability of ClO2 as a modern, non-destructivesanitising option that addresses microbiological safety concerns whilemeeting the hygienic and regulatory requirements related to table eggproduction. Further research is recommended to assess the internalquality of eggs and to explore broader microbiological indicatorsunder varying storage and environmental conditions.
Keywords: Disinfection; eggshell; egg quality; EU legislation; stable liquid chlorine dioxide